Riparian Vadose Zone Preferential Flow: Review of Concepts, Limitations, and Perspectives - Orozco-López, E. (2020)
While theories exist for modeling preferential flow processes, experimental and modeling techniques are still lacking to characterize in situ RVZ macropore network morphologies at the soil profile and landscape scales. Importantly, the presence of a seasonal SWT can increase MF and transport processes neglected in current analyses. Additional research is needed to evaluate holistic modeling frameworks that can represent MF from measurable parameters at the riparian field scale. In this work, we review various MF theories and concepts suitable to RVZ conditions and identify current limitations and knowledge gaps. We emphasize the use of dual‐permeability approaches as a compromise between model complexity and parameter identifiability. We also identify the need for well‐controlled experimental studies using the latest monitoring technology and validation studies at the laboratory and field scales. Only then can decision‐support tools realistically predict the influence of preferential flow processes on the performance of riparian buffers as a surface water quality control practice.